Thomas Hobbes Leviathan a critical edition - Hobbes, Thomas 1588-1679 (Continuum, 2005)
By a deep and careful analysis of the text, enabling a new printing history of Leviathan to be constructed, this edition demonstrates that the traditional picture is substantially wrong. Both the Bear and Ornaments editions contain corrections and changes by Hobbes himself and are therefore central to reconstructing his text. In their substantial Introduction the editors examine all previous editions of Leviathan (as well as the manuscript copy prepared for Hobbes as a presentation copy for the King), throwing light on its history and calling into question the assumptions of previous editors
In two volumes
Keywords: Hobbes, Thomas 1588-1679 / Leviathan (Hobbes, Thomas); Hobbes, Thomas / 1588-1679 / Leviathan; Leviathan (Hobbes, Thomas); Political science / Early works to 1800 / Philosophy; State, The / Early works to 1800; Political science / Philosophy / Early works to 1800; BIOGRAPHY & AUTOBIOGRAPHY; Political; POLITICAL SCIENCE; Essays; POLITICAL SCIENCE; Government; General; POLITICAL SCIENCE; Government; National; POLITICAL SCIENCE; Reference; Political science; Philosophy; State, The; Early works; Electronic books / Early works